Profiling Scientific Literacy of Biology Education Students in Distance Higher Education - Dyah Aniza Kismiati; Ahmad Yani; Nafila Widiyana; Dian Sudi Hadiningrum (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Scientific literacy is a key competence in the 21st century, enabling students to understand scientific concepts, engage in inquiry, reason with evidence, and address sociocentric issues. This study aimed to profile the scientific literacy of biology education students in distance higher education by identifying their strengths and weaknesses across four dimensions: conceptual understanding, scientific inquiry, evidence and reasoning, and sociocentric issues. A quantitative survey design was employed involving 167 students in the Biology Education Study Program of a distance higher education institution. Data were collected using a 15-item Scientific Literacy Survey developed based on Bybee’s (2009) framework, rated on a four-point Likert scale (1 = strongly disagree to 4 = strongly agree). Descriptive statistics and Latent Profile Analysis (LPA) were applied to analyze students’ competencies. The descriptive results indicated that students possessed moderate scientific literacy, with mean scores ranging from 2.93 to 3.19. Conceptual understanding (M = 3.15) and sociocentric issues (M = 3.08) were the strongest domains, while scientific inquiry (M = 2.97) and evidence and reasoning (M = 3.00) emerged as weaker areas. LPA revealed three distinct groups: High Balanced Literacy (32%), Moderate Conceptual but Weak Inquiry (48%), and Low Across All Aspects (20%). These findings suggest that while students are capable of connecting scientific knowledge to real-world contexts, they face challenges in inquiry and reasoning. The study recommends the integration of virtual laboratories, project-based learning, and sociocentric case discussions to strengthen inquiry skills and foster scientifically literate graduates prepared for 21st-century challenges